(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2018)
The present study was conducted to investigate the effect of different concentrations( 10% 20% 30%) of phosphate solubilizing bacteria (PSB) on seed germination, plant growth and proline content in nodules and leaves of mung bean (Vigna radiata L.). An experiment was carried out with the seeds obtained of mung bean sown in field with PSB and without PSB. The results reveal on overall increase in all parameters in the inoculated plants than their comparable uninoculated ones. Phosphate solubilizing bacteria with 30% concentration, on Vigna radiata(L.) showed the higher effect on seed germination, plant growth, fresh and dry matter, protein, leghaemoglobin and chlorophyll content as compared to 10% 20% concentration of phosphate solubilizing bacteria.